Analisis Yuridis terhadap Pengaturan Perlindungan Data Pribadi dalam Layanan Fintech Peer-To-Peer Lending - Komang Dian Andayani (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Advances in information technology-based financial services are beginning to follow suit, in the form of peer-to-peer lending, which provides easy access to loans without the need for conventional financial institutions. However, this convenience brings new challenges, particularly regarding the protection of users' personal data. Many platform providers access excessive amounts of sensitive information, such as contacts, photos, and other personal data, which can be misused to the detriment of borrowers. Therefore, this study aims to identify and analyze regulations related to personal data protection, particularly in the field of peer-to-peer lending services in Indonesia. It also analyzes the role of financial institutions, namely the Financial Services Authority (OJK), in addressing potential violations committed by platform providers. Using a normative legal approach, the study shows that despite the existence of these regulations, implementation in the field is suboptimal, particularly in terms of monitoring illegal platforms. Furthermore, challenges to oversight include limited resources and a lack of digital literacy among the public, which results in many users not fully understanding the risks of sharing their personal data. This study also highlights the importance of collaboration between the OJK, the Ministry of Communication and Information Technology, and law enforcement agencies to strengthen oversight mechanisms and take action against violations. In addition, extensive public education regarding personal data security is needed to encourage greater vigilance in using digital services. Personal data protection must be a top priority in the development of financial technology to prevent privacy violations. Strict regulations and effective sanctions are expected to provide a deterrent effect and create a healthy and equitable fintech ecosystem in Indonesia. This study also recommends that the government accelerate harmonization between the Personal Data Protection Law (PDP Law) and financial services sector regulations, particularly regarding service providers' transparency obligations in managing consumer data.